The evolving role of whole-exome sequencing in the management of disorders of sex development. Issue 6 (16th June 2021) - Tenenbaum-Rakover, Yardena; Admoni, Osnat; Elias-Assad, Ghadir; London, Shira; Noufi-Barhoum, Marie; Ludar, Hanna; Almagor, Tal; Zehavi, Yoav; Sultan, Charles; Bertalan, Rita; Bashamboo, Anu; McElreavey, Kenneth
Abstract : Objective: Disorders of sex development (DSD) are defined as congenital conditions in which the development of chromosomal, gonadal and anatomical sex is atypical. Despite wide laboratory and imaging investigations, the etiology of DSD is unknown in over 50% of patients. Methods: We evaluated the etiology of DSD by whole-exome sequencing (WES) at a mean age of 10 years in nine patients for whom extensive evaluation, including hormonal, imaging and candidate gene approaches, had not identified an etiology. Results: The eight 46, XY patients presented with micropenis, cryptorchidism and hypospadias at birth and the 46, XX patient presented with labia majora fusion. In seven patients (78%), pathogenic variants were identified for RXFP2, HSD17B3, WT1, BMP4, POR, CHD7 and SIN3A. In two atients, no causative variants were found. Mutations in three genes were reported previously with different phenotypes: an 11-year-old boy with a novel de novo variant in BMP4 ; such variants are mainly associated with microphthalmia and in few cases with external genitalia anomalies in males, supporting the role of BMP4 in the development of male external genitalia; a 12-year-old boy with a known pathogenic variant in RXFP2, encoding insulin-like 3 hormone receptor, and previously reported in adult men with cryptorchidism; an 8-year-old boy with syndromic DSD had a de novo deletion in SIN3A . Conclusions: Our findings of molecular etiologies for DSD in 78% of our patients indicate a major role for WES in early DSD diagnosis and management – and highlights the importance of rapid molecular diagnosis in early infancy for sex of rearing decisions.